2006
DOI: 10.1038/sj.jhh.1002047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on 24-h ambulatory blood pressure and target organ damage

Abstract: Differences between male and female subjects in mean 24 h blood pressure (BP) values and target organ damage such as left ventricular mass (LVMASS) and intima-media thickness (IMT) of carotid arteries were explained. The study population consisted of 1445 subjects. All subjects underwent 24 h ambulatory BP monitoring, left ventricular echocardiography and measurement of IMT of carotid arteries. Men and women did not differ in age, body mass index (BMI) and clinic BP values. Mean 24 h systolic and diastolic BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…[15][16][17] One of the studies that established the efficacy of the olmesartan/amlodipine combination used a nonresponder design. Patients who failed to achieve an adequate level of BP control after 8 weeks' treatment with amlodipine (5 mg per day) were randomized to 8 weeks of treatment with one of three dose combinations of olmesartan (10,20 or 40 mg per day) plus amlodipine (5 mg per day), or to continue with amlodipine (5 mg) monotherapy. The study also included a further 8-week period of double-blind treatment, in which patients with suboptimal BP control had their treatment uptitrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] One of the studies that established the efficacy of the olmesartan/amlodipine combination used a nonresponder design. Patients who failed to achieve an adequate level of BP control after 8 weeks' treatment with amlodipine (5 mg per day) were randomized to 8 weeks of treatment with one of three dose combinations of olmesartan (10,20 or 40 mg per day) plus amlodipine (5 mg per day), or to continue with amlodipine (5 mg) monotherapy. The study also included a further 8-week period of double-blind treatment, in which patients with suboptimal BP control had their treatment uptitrated.…”
Section: Introductionmentioning
confidence: 99%
“…The study also provides an opportunity to ascertain whether the combination is effective in specific patient groups. For example, certain BP-lowering treatment regimens have been reported to differ between men and women, [18][19][20] whereas others have shown no evidence of a gender difference. 21 Also, BP is known to increase with advancing age and it is important to determine that antihypertensive therapies are effective in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent research has confirmed that male sex was associated with higher ambulatory BPs and associated target organ pathology in contrast to a group of female patients matched on age, body mass index (BMI), smoking and cholesterol status and clinic BP. 26 It is well established that obesity is linked to high BP, 1 regardless of whether it is measured in the clinic or via ambulatory monitoring. Obesity has also been recently linked with an increased incidence of WCEs, but a decreased incidence of RWCEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the univariate correlation coefficients for detecting WCE from home BP monitoring were so small, it seems highly unlikely that patient self-monitoring would contribute to its prediction even with a substantially larger sample. Research examining the relation between several demographic variables, like sex, obesity and smoking status, have typically employed much larger samples 26,27 than the sample used in the present study. It is quite likely that our sample size limited us in making comparisons with these previous studies using larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…4 Non-dipping hypertension is associated with a higher risk of stroke, congestive heart failure, renal insufficiency, obstructive sleep apnoea and lower socioeconomic class. [5][6][7][8] Urate has been shown to be a powerful risk marker for all-cause mortality in untreated subjects with essential hypertension, 9 and is known to be an independent predictor of poor outcome and future vascular events in acute stroke. 10 Since both increased urate and hypertension (either office or ambulatory) are associated with the same disease processes, it would be expected that the two would tend to be associated with each other.…”
mentioning
confidence: 99%